2017
DOI: 10.1590/s1806-37562016000000162
|View full text |Cite
|
Sign up to set email alerts
|

Smoking among female sex workers: prevalence and associated variables

Abstract: Objective: To assess the prevalence of smoking and associated variables in female sex workers (FSWs) Methods: This was a quantitative cross-sectional study involving FSWs in the city of Botucatu, Brazil, who completed a sociodemographic questionnaire, including data regarding smoking status, motivational stage of change, and degree of nicotine dependence, as well as the Perceived Stress Scale and the Hospital Anxiety and Depression ScaleResults: We included 83 FSWs. The mean age was 26.8 years. Among the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
6
0
3
Order By: Relevance
“…The pooled prevalence of depression among FSWs from LMICs is 41.8% (95% CI 35.8%–48.0%). Seven studies reported on the prevalence of anxiety among FSWs [ 9 , 32 , 33 , 50 , 58 , 64 , 70 ], with 3 included in the meta-analysis ( Fig 3 ). The pooled prevalence of anxiety among FSWs from LMICs is 21.0% (95% CI 4.8%–58.4%).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled prevalence of depression among FSWs from LMICs is 41.8% (95% CI 35.8%–48.0%). Seven studies reported on the prevalence of anxiety among FSWs [ 9 , 32 , 33 , 50 , 58 , 64 , 70 ], with 3 included in the meta-analysis ( Fig 3 ). The pooled prevalence of anxiety among FSWs from LMICs is 21.0% (95% CI 4.8%–58.4%).…”
Section: Resultsmentioning
confidence: 99%
“…(26) . Neste estudo, a média de cigarros consumidos por dia foi entre 22 e 24, fato este que corrobora com pesquisas nacionais que apontam os mesmos resultados no decorrer das análises estatísticas (26)(27)(28) .…”
Section: Discussionunclassified
“…nicotina elevada e muito elevada, necessitando além de um alto grau de motivação, uma abordagem cognitiva comportamental e também medicamentosa para a cessação do tabagismo (6,14,16,27,29) . Grande parte dos indivíduos tabagistas caracteriza-se pela alta taxa de cigarros consumidos por dia em conjunção com a dependência tanto física, quanto psicológica, fato este, que associado muitas vezes a baixa escolaridade, contribui negativamente para que o grau de dependência relacionada à nicotina seja extremamente alto.…”
Section: Discussionunclassified
“…In order to make such an epidemiological assessment, the article entitled "Smoking among female sex workers: prevalence and associated variables", 7 published in the current issue of the JBP, focuses on a specific subgroup of the Brazilian population that fits perfectly among the women most vulnerable to addiction. The authors were very happy in their choice of this object of study to describe the characteristics and prevalence of smoking in this population subgroup, a prevalence that was found to be much higher than the mean prevalence reported for the general Brazilian population (71.1% vs. 10.4%).…”
mentioning
confidence: 99%
“…In conclusion, it is important to note that, by establishing the behavior of female sex workers regarding tobacco use, the study by Devóglio et al 7 raises a fundamental issue, which is that of structured planning developed specifically to address this highest risk subgroup. Therefore, not only should a cognitive behavioral approach and the use of pharmacotherapy be considered to improve the quality of life of these women but also the use of a harm reduction strategy.…”
mentioning
confidence: 99%